Pelaksanaan Peraturan Walikota Denpasar Nomor 36 Tahun 2018 tentang Pengurangan Penggunaan Kantong Plastik - Ni Luh Yuni Setyawati; I Ketut Kasta Arya Wijaya; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2021)
Plastic waste is one of the causes of environmental problems. Therefore, the Denpasar City Government issued a Mayor Regulation on Reducing the Use of Plastic Bags. The purposes of this study are to reveal the implementation of the Denpasar Mayor Regulation Number 36 of 2018 concerning Reducing the Use of Plastic Bags and the inhibiting factors in the implementation of the Mayor's Regulation Number 36 of 2018. The type of research used is empirical legal research with a statutory approach. The technique of collecting legal materials is done by observation, interviews and documentation methods. Sources of data used are primary and secondary data sources. After the data was collected, the data were analyzed using descriptive analysis techniques. The results of the discussion revealed that the Mayor's regulation was formed with the aim of controlling environmental damage and ensuring the sustainability of living things. The implementation of this regulation has not been effective because there are still many business actors and people who use plastic bags without replacing them with alternative bags. Inhibiting factors in the implementation of Denpasar Mayor Regulation No. 36 of 2018, namely the lack of public awareness of the dangers posed by the use of single-use plastic bags, the existence of the covid-19 pandemic which hinders government programs in directly socializing this regulation. Efforts that can be made by the government in socializing the reduction of plastic use can only be done virtually through mass media in the form of radio and television.